A Digital Image Steganographic Detection Method for LSB Steganography - Zhang, Jiaqi; Zhang, Dongpo; Zhang, Shang (International Journal of Computer Science and Information Technology, 2024)
With the advancement of communication technology, communication information can no longer be transmitted merely through text but can be covertly conveyed via various types of communication carriers like images, audio, and video. This brings forth new challenges to traditional detection techniques that mainly target text information. Digital image steganalysis aims to detect and uncover communication information by recognizing steganographic behaviors contained within digital image files. This paper takes digital image steganographic activities based on least significant bit (LSB) as the main research object and conducts analysis and identification of digital images with steganographic information through visual attack method. It has been verified through experiments that steganographic activities based on LSB are hardly detectable through direct visual observation, but can be identified visually after undergoing visual attack processing.